Competitive situations requiring mental toughness in women`s australian rules football - Clark, J. D.; Mallett, C. J.; Moyle, G. M.; Coulter, T. J. (Journal of Sports Sciences, 2023)
In the last decade, mental toughness (MT) researchers have been interested in the behaviours exemplifying MT. Despite this interest, little attention has been paid to the competitive situations these behaviours occur in. Hence, the aim of the current study was to start addressing this gap by comprehensively focusing on the situations requiring MT in sport - specifically, the contextual demands linked to MT in women`s Australian rules football. Focus groups and individual semi-structured interviews were conducted at two Australian rules football clubs after each competitive round of the 2020 season. Following analysis of participant responses, three broad situational categories were created, representing the psychological demands required by the player or team to successfully overcome in-game challenges. These categories were: context intelligence, attentional regulation, and emotional regulation. This study identified that situations requiring MT also required a degree of acceptance and commitment - alluding to a potential link between acceptance-commitment therapy (ACT) and MT. Conceptually, this view offers a new perspective on the psychological process of being mentally tough in competition. The link between ACT and MT also offers an avenue for MT development. Recommendations are made for incorporating these identified situations into regular training sessions following affective learning design principles.